A self-assembled nanoparticle platform based on poly(ethylene glycol)–diosgenin conjugates for co-delivery of anticancer drugs. Issue 91 (9th October 2015) - Li, Chunxiao; Dai, Lin; Liu, Kefeng; Deng, Lihong; Pei, Tingting; Lei, Jiandu
<x xml:space="preserve">Abstract</x> We developed a nanoparticle platform based on poly(ethylene glycol)–diosgenin (mPEG–DGN) conjugates for co-delivery of anticancer drug HCPT.